Transition from Index to Symbol in Language - ABRAHAMYAN, ASHOT (Bulletin of Yerevan University B: Philology, 2021)
The propositions that naming is performed on the basis of the properties of the named realia and that the word consists of morphemes, allow us to conclude that the morpheme is actually the designation of the given realia’s property. The meaning of the property does not exhaust the content of the morpheme fully; it is rather its primary and most essential component, besides which there exists another one – a somewhat blurred and still existing phonetic meaning of sounds that are constituents of the morpheme. From the point of view of referential (extralinguistic) meaning the morpheme can be characterized as a symbol (according to Ch. S. Peirce’s terminology). However, the full semiotic characteristics of the morpheme should also take into account the intralinguistic meaning, based on the meanings of its components, thus acknowledging not only the symbolic but also the index aspect of the morpheme.
Keywords: morpheme, sound, symbol, index, intralinguistic meaning, referential meaning, property, structure